Mucoid Pseudomonas aeruginosa and regional inflammation in the cystic fibrosis lung - Malhotra, Sankalp (J Cyst Fibros, 2019)
BACKGROUND: Pseudomonas aeruginosa is the prominent bacterial pathogen in the cystic fibrosis (CF) lung and contributes to significant morbidity and mortality. Though P. aeruginosa strains initially colonizing the CF lung have a nonmucoid colony morphology, they often mutate into mucoid variants that are associated with clinical deterioration. Both nonmucoid and mucoid P. aeruginosa variants are often co-isolated on microbiological cultures of sputum collected from CF patients. With regional variation in bronchiectasis, tissue damage, inflammation, and microbial colonization, lobar distribution of nonmucoid and mucoid P. aeruginosa variants may impact local microenvironments in the CF lung, but this has not been well-studied. METHODS: We prospectively collected lobe-specific bronchoalveolar lavage (BAL) fluid from a CF patient cohort (n=14) using a standardized bronchoscopic protocol where collection was performed in 6 lobare regions. The lobar BAL specimens were plated on P. aeruginosa-selective media and proinflammatory cytokines (IL-1, TNF, IL-6 and IL-8) were measured via cytokine array. Correlations between infecting P. aeruginosa variants (nonmucoid, mucoid, or mixed-variant populations), the lobar regions in which these variants were found, and regional proinflammatory cytokine concentrations were measured. RESULTS: P. aeruginosa mucoid and nonmucoid variants were homogenously distributed throughout the CF lung. However, infection with mucoid variants variants (found within single-or mixed-variant populations) was associated with significantly greater regional inflammation. The upper and lower lobes of the CF lung did not exhibit differences in inflammatory cytokine concentrations. CONCLUSIONS: Mucoid P. aeruginosa infection is a microbial determinant of regional inflammation within the CF lung.